COMMUNITY EMPOWERMENT EFFECTIVENESS IN WASTE MANAGEMENT WITH MAGGOT BSF BIOCONVERSION IN TANGERANG CITY - Asropi Asropi; Marlinda Erfanti; Aini Timur (DIA: Jurnal Administrasi Publik, 2023)
Waste problems in big cities is something that is often faced, as well as in the city of Tangerang. Garbage is a continuous problem that requires the active role of the community in solving it. The Tangerang City Government has carried out recycling activities with Black Soldier Flies (BSF) bioconversion in managing waste which is a form of innovation by empowering the community. For this reason, it is necessary to carry out evaluations and strategies through the theory of effectiveness seen from the aspects of achieving goals, integration and adaptation in order to see results and measure the achievements of the programs implemented and the benefits for the community. In this study using a qualitative descriptive analysis method by describing the circumstances and phenomena that occur as well as problems by conducting interviews, observations, and published documents and information. The research interviews were conducted with representatives of the Tangerang City government, environmental activists (Indonesian Benua Lestari Foundation), Jatiuwung ITF officers, and the community who received maggot cultivation training. The results obtained in the implementation of community empowerment in processing organic waste with BSF bioconversion when viewed from the aspect of achieving goals, integration and adaptation have not been effective.